Literature study on the uses and risks of nanomaterials as pigments in the European Union (Helsinki, 2018)
"This report provides a review on the safe use of nano-sized pigments when used by professionals, workers or consumers. Extensive literature searches were carried out in combination with analyses of data from national nano-inventories to capture the current state of play. The report provides a list of nano-sized pigments currently identified on the EU market and discusses potential risks arising from their use in paints, coatings, printer toner cartridges, personal care products, tattooes as well as other potential uses of nanopigments. Data for hazard and risk assessment are not available for the vast majority of identified nanopigments. Evidence-based conclusions on the safety of most nanopigments uses cannot be drawn, however, some general observations and conclusions can be derived. Dry pigments present the highest concern because they can be easily inhaled and ingested. Exposures to nano-sized pigments that are integrated into polymer, paint or coating matrices are not thought to be significant, and the risks to consumers from such uses are low. The report also discusses uncertainties associated with the identification of nanopigments (and nanomaterials in general), measurements of exposure to nano-sized pigments and methods of toxicity testing."